Preparation and Characterization of MgO-Modified Rice Straw Biochars - Qin, Xianxian (Molecules, 2020)
Rice straw is a common agricultural waste. In order to increase the added value of rice straw and improve the performance of rice straw biochar. MgO-modified biochar (MRBC) was prepared from rice straw at different temperatures, pyrolysis time and MgCl(2) concentrations. The microstructure, chemical and crystal structure were studied using X-ray diffraction (XRD), a Scanning Electron Microscope (SEM), Fourier transform infrared spectroscopy (FTIR), nitrogen adsorption desorption isotherms and Elementary Analysis (EA). The results showed that the pyrolysis temperature had significant influence on the structure and physicochemical property of MRBCs. MRBC-2 h has the richest microporous structure while MRBC-2 m has the richest mesoporous structure. The specific surface area (from 9.663 to 250.66 m(2)/g) and pore volume (from 0.042 to 0.158 cm(3)/g) of MRBCs increased as temperature rose from 300 to 600 °C. However, it was observed MgCl(2) concentrations and pyrolysis time had no significant influence on pore structure of MRBCs. As pyrolysis temperature increased, pH increased and more oxygen-containing functional groups and mineral salts were formed, while MgO-modified yield, volatile matter, total content of hydrogen, oxygen, nitrogen, porosity and average pore diameter decreased. In addition, MRBCs formed at high temperature showed high C content with a low O/C and H/C ratios.